Macrophage Migration Inhibitory Factor Mediates Neuroprotective Effects by Regulating Inflammation, Apoptosis and Autophagy in Parkinson's Disease. (15th September 2019) - Li, Siying; Nie, Kun; Zhang, Qingxi; Guo, Manli; Qiu, Yihui; Li, You; Gao, Yuyuan; Wang, Lijuan
Abstract: The influence of neuroinflammation in the development and progression of Parkinson's disease (PD) remains unknown. Macrophage migration inhibitory factor (MIF) is a multipotent and key cytokine involved in the pathogenesis of acute and chronic inflammatory and immune disorders. The aim of this study was to investigate the neuroprotective effects mediated by MIF in PD. Cellular apoptosis was measured by RT-qPCR analysis, fluorescence-activated cell sorting (FACS) analysis and western blotting. JC-1 staining was used to analyze the mitochondrial membrane potential (MMP). The formation of autophagosomes was detected by western blot analysis. Autophagic flux was assessed by tandem mRFP-GFP-LC3 fluorescence microscopy. Expression of MIF, cleaved-PARP and LC3B-II was increased significantly in both acute and chronic PD animal models. MIF was positively associated with IL-10 ( P < 0.001), but inversely with TNF-α ( P < 0.05). The PD cells (1 mM MPP + treated group) showed an increase in early-apoptotic cells by FACS. Upregulating MIF expression resulted in a lower concentration of cleaved-PARP than the control group ( P < 0.001). The MMP was higher in the MIF upregulated group than in the MIF knockdown group ( P < 0.001). Upregulating MIF expression resulted in a higher concentration of LC3B-II than the control group ( P < 0.001). Finally, LC3 puncta were markedly increased in the MIF upregulated group and in the MIF + MPP + group. This study indicates that MIF mediates a neuroprotective effect via suppressing inflammatory responses, inhibiting apoptosis and inducing autophagy in PD. Highlights: Take the lead in verifying MIF mediate neuroprotective effects. The protective effects work by inhibiting apoptosis and inducing autophagy in PD. MIF suppresses inflammatory response and inhibits PD cell apoptosis by increasing MMP. MIF mediates an antagonistic effect of apoptosis and autophagy in PD.